VEGFA rs3025020 Polymorphism Contributes to CALR-Mutation Susceptibility and Is Associated with Low Risk of Deep Vein Thrombosis in Primary Myelofibrosis - Villani, Laura; Rosti, Vittorio; Massa, Margherita; Campanelli, Rita; Catarsi, Paolo; Carolei, Adriana; Abbà, Carlotta; de Silvstri, Annalisa; Gale, Robert Peter; Barosi, Giovanni (TH Open, 2021)
Background Single nucleotide polymorphisms (SNPs) in vascular endothelial growth factor A (VEGFA) are associated with susceptibility to several diseases including cancer. Correlations between VEGFA rs3025020 genotypes with clinical and laboratory features of primary myelofibrosis (PMF) are unstudied.Methods DNA was analyzed by real-time polymerase chain reaction for VEGFA rs3025020 genotypes in a cohort of 844 subjects with PMF and in two cohorts of normal subjects (N = 247 and N = 107).Results Frequency of rs3025020 minor allele (T) was not significantly different in subjects with PMF compared with normals; however, the T-allele was more frequent in PMF subjects with a calreticulin (CALR)-mutated genotype compared with normals (35 vs. 27%; OR = 1.47 [95% CI, 1.09, 1.98] p = 0.011), especially in subjects with a CALR-type 2/type 2-like mutation (43 vs. 27%; OR = 2.01 [1.25, 3.24] p = 0.004). CALR mutants with the rs3025020 TT genotype had higher CXCR4 expression on CD34-positive blood cells, and those who carried CT/TT genotypes had lower platelet concentrations compared with other genotypes at diagnosis. Overall, subjects with the rs3025020 CT/TT genotype had a lower cumulative incidence of deep vein thrombosis in typical sites (1.6 vs. 4.2%; OR = 0.37 [0.15, 0.90] p = 0.029) and longer interval from diagnosis to first thrombosis (HR = 0.37 [0.14, 0.95] p = 0.039).Conclusion Persons with PMF and the VEGFA rs3025020 minor T-allele are more likely to have a CALR mutation compared with other somatic driver mutations and lower cumulative incidence and hazard for deep vein thrombosis in typical sites.
Keywords: primary myelofibrosis; VEGFA polymorphism; rs3025020; deep vein thrombosis; CALR mutation